Sequence Control Mechanism for the Handover of Distribution Networks Under Disaster Recovery - Cheng Long; Jian Zhang; Hua Zhang; Xing Liu; Yiwen Gao; Xueneng Su; Shilong Li (IEEE Access)
In the distribution network under the background of disaster, the distribution terminal embodies the characteristics of disorder. Therefore, when the distribution terminal node accesses the backup network, there will be congestion, delay and other phenomena. In order to solve this problem, this paper proposes a distribution terminal access mechanism based on sequence control. Then, a family of control sequences is constructed based on the trace function in the finite field. The control sequences can realize the rapid access of distribution terminal node users and the safe transmission without interference. Finally, the program algorithm for the process of distribution terminal node accessing and exiting the backup network based upon the control sequences is given. The fast and stable information transmission of distribution terminal node can be realized by means of the sequence control mechanism.